Oxford English dictionary - Simpson, John (Clarendon Press,Oxford University Press, 1997)
This is the third in a major series of volumes supplementing the Second Edition of the Oxford English Dictionary. Volume 3 contains 3,000 new words and meanings from around the English-speaking world, including the UK (Citizen's Charter), North America (affluential, Clintonomics), Australia (beardie), and the West Indies (zouk)